STATUS GIZI, ASUPAN SERAT DAN NATRIUM PADA PASIEN HIPERTENSI RAWAT JALAN DI RSUP SANGLAH DENPASAR - Desak Made Mentari Dewi Riesha; Pande Putu Sri Sugiani; Ni Komang Wiardani (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Abstract. Dietary fiber intake which appropriate with recommended allowance can depend hypertension by decrease cholesterol utilisation in intestinal. So, the buildup of cholesterol in blood vessel as the caution of hypertension can be avoid. On the other side, the high sodium intake cause the increase of sodium concentration in extracelluler liquid and the volume of blood is increase too.The aimed of study is to determine the nutritional status, the dietary fiber and sodium intake in hypertension outpatients at Sanglah hospital.The type of research is observational and cross-sectional design. Data were collected by measure the weight and height directly to determine the nutritional status of the patients. Dietary fiber and sodium intake were determine by using Semi Quantitative Food Frequency Questioner (SQ-FFQ). Based on analysis data of 43 samples, there were three samples (6,98%) had overweight, seven samples (16,27%) had obesity and thirty three samples had normal weight. Mainly samples amount 37 samples (86,05%) had dietary fiber intake which not appropriate with recommended allowance. There were 23 samples (53,49 %) had a high sodium intake. Based on analysis data between nutritional status and hypertension, indicated that nutritional status were not giving a big effect with the level of hypertension cause there are the others factor such as excessive alcohol consumption, physical activity, stress and smoking which also give an impact to hypertension.Keyword: dietary fiber, hypertension, nutritional status, sodium